If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + y = xy Solving 3x + y = xy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1xy' to each side of the equation. 3x + -1xy + y = xy + -1xy Combine like terms: xy + -1xy = 0 3x + -1xy + y = 0 Add '-1y' to each side of the equation. 3x + -1xy + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 3x + -1xy + 0 = 0 + -1y 3x + -1xy = 0 + -1y Remove the zero: 3x + -1xy = -1y Combine like terms: -1y + y = 0 3x + -1xy + y = 0 The solution to this equation could not be determined.
| p^2+2p=35 | | 7x+6y-1=0 | | 71n+1.7=-3n+5773.7 | | 0.3x^2+2y^2-6=0 | | k^2=15+2k | | .3(2b+9)=.6(b+4.5) | | 3-2*(x+3)=x-18 | | m^2=4m+12 | | 5x+3=6x+1 | | 2x+27=4+x | | 1.5-12-3z=-10 | | -1.5+6+9z=3 | | -7z-14=-10z+16 | | 12(4x+6)+x=-26 | | (3x+20)=(5x+50) | | 2x+1=2-1 | | 16p-4=8(2p-3) | | 3(2-x)=3-(3-x) | | 3/8=a+4/5 | | -5x+24=x | | 6x=-43 | | 2-6y+3=3y+14-6y | | -1.2=-4.79+n | | 15x+22+2=180 | | 486+.03a=490+.02a | | 12(m+3)+5m=70 | | -3=x+(-1) | | 15x+22=180 | | 8y+14=3y+49 | | -14=q-18 | | 67=7-3(5x-10) | | 6(x+7)x=9 |